Tinjauan perundang-undangan di Indonesia dan politik Islam tentang sumber dana kampanye - Rajab, Iqbal Najib (Maliki Interdisciplinary Journal, 2024)
This article examines the legislation in Indonesia that regulates the sources of campaign funds and analyzes it from an Islamic political perspective. The main focus of the discussion includes the evolution of campaign finance regulations in Indonesia, in-depth analysis of Law Number 7 of 2017 concerning General Elections, and case studies of violations and implementation of regulations. In addition, this article discusses the principles of justice and transparency in Islam, by referring to relevant verses of the Koran and Hadith, as well as the views of ulama regarding campaign financing. From this analysis, it was found that although regulations in Indonesia are quite comprehensive, implementation still faces various challenges. The integration of Islamic principles in campaign financing regulations can help create a fairer and more transparent system, supporting a democratic process of quality and integrity